2006
DOI: 10.1161/01.str.0000226902.43357.fc
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery

Abstract: Background and Purpose-Understanding brain plasticity after stroke is important in developing rehabilitation strategies.Active movement therapies show considerable promise but depend on motor performance, excluding many otherwise eligible patients. Motor imagery is widely used in sport to improve performance, which raises the possibility of applying it both as a rehabilitation method and to access the motor network independently of recovery. Specifically, whether the primary motor cortex (M1), considered a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
288
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 603 publications
(310 citation statements)
references
References 124 publications
7
288
0
5
Order By: Relevance
“…Mainly due to this difference, motor imagery resembles motor execution best in patients, but only second-best in HVs. While the reasons for this difference are unclear, it is interesting to note that while the involvement of the primary motor cortex in motor imagery is highly variable and debated in HVs (Dechent et al, 2004;Jackson et al, 2001;Sharma et al, 2006Sharma et al, , 2008, patient studies seem to show primary motor cortex involvement more consistently (Lehericy et al, 2004;Kimberley et al, 2006;Sharma et al, 2009aSharma et al, , 2009b. A reason for this may be that motor imagery is more difficult for patients so that additional neural resources are recruited for task performance.…”
Section: Motor Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…Mainly due to this difference, motor imagery resembles motor execution best in patients, but only second-best in HVs. While the reasons for this difference are unclear, it is interesting to note that while the involvement of the primary motor cortex in motor imagery is highly variable and debated in HVs (Dechent et al, 2004;Jackson et al, 2001;Sharma et al, 2006Sharma et al, , 2008, patient studies seem to show primary motor cortex involvement more consistently (Lehericy et al, 2004;Kimberley et al, 2006;Sharma et al, 2009aSharma et al, , 2009b. A reason for this may be that motor imagery is more difficult for patients so that additional neural resources are recruited for task performance.…”
Section: Motor Imagerymentioning
confidence: 99%
“…This question was motivated from a clinical perspective, as we followed the suggestion that motor system activation is beneficial for motor recovery (Johnson-Frey, 2004;Munzert et al, 2009;Sharma et al, 2006). In this section, we will focus more on the scientist's perspective and scrutinize in more detail the potential underlying processes giving rise to the observed activation patterns.…”
Section: Comparison Of Movement Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the brain substrates of motor imagery, i.e. mental rehearsal in one's mind's eye of a movement, and have found that motor imagery activates to a large extent the same brain networks involved in motor execution, including parts of the SMA, the dorsal premotor cortex, the posterior parietal cortex, the cerebellum and M1 in certain conditions (Lui et al, 2008;Gao et al, 2011;Raffin et al, 2012), showing the potential role of motor imagery in motor rehabilitation (Sharma et al, 2006). Recent functional neuroimaging studies, using region of interest analyses, however, have shown a specific pattern associated with motor execution and imagery (Raffin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealing the strong relationship between motor simulations and motor system activation, functioning independently of motor performance (Abbruzzese et al, 1999, Bonnet et al, 1997, Decety, 1996, Fadiga et al, 1999, Jeannerod, 1995, Jeannerod, 2001, Porro et al, 1996and Schnitzler et al, 1997 have given rise to the hope that motor imagery will provide a backdoor to the motor system after impairments (Jackson et al, 2001, Lehéricy et al, 2004and Sharma et al, 2006. To this end, motor imagery has been shown in neurofeedback task paradigms to increase regional cortical activation: long-term effects of increased activation of motor areas involving neural circuitries associated with motor skill learning can last up to several days (Kober et al, 2014 andYoo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%